2001
DOI: 10.5194/aab-44-621-2001
|View full text |Cite
|
Sign up to set email alerts
|

Wachstum, Schlachtleistung und Schlachtkörperqualität von Weidemastkälbern aus der Mutterkuhhaltung mit Fleischrindrassen

Abstract: SummaryTitle of the paper: Growth, slaughter Performance and meat quality of pasture fattening calves raised on cattle out ofthe mother cows with beef cattle The production of calves raised on cattle depends on mother cows and the direct market. The calves mainly live on mother's milk, some cattle fodder and a little grain from the farm. Out of this reason and because ofthe high quality ofthe product it has a high reputation for the consumer. Some other advantages are for the method, the producer and the natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
1
0
4
Order By: Relevance
“…die Fettgewebeklassen 2 und 3. Dies begünstigt den Einsatz von großrahmigen und speziellen Mastrassen für die Fleischproduktion (FRELICH et al, 1998;KÖGEL et al, 2000;GOLZE, 2001;CHAMBAZ et al, 2001a, b;REICHARDT et al, 2002;JACUBEC et al, 2003). Weitere Fragen der Fleischrinderhaltung ist der Kostenaspekt und die hohen Qualitätsansprüche der Verbraucher (ENDER et al, 2000;CHAMBAZ et al, 2001a, b;REICHARDT et al, 2002;SURBT et al, 2006).…”
unclassified
See 3 more Smart Citations
“…die Fettgewebeklassen 2 und 3. Dies begünstigt den Einsatz von großrahmigen und speziellen Mastrassen für die Fleischproduktion (FRELICH et al, 1998;KÖGEL et al, 2000;GOLZE, 2001;CHAMBAZ et al, 2001a, b;REICHARDT et al, 2002;JACUBEC et al, 2003). Weitere Fragen der Fleischrinderhaltung ist der Kostenaspekt und die hohen Qualitätsansprüche der Verbraucher (ENDER et al, 2000;CHAMBAZ et al, 2001a, b;REICHARDT et al, 2002;SURBT et al, 2006).…”
unclassified
“…Weitere Fragen der Fleischrinderhaltung ist der Kostenaspekt und die hohen Qualitätsansprüche der Verbraucher (ENDER et al, 2000;CHAMBAZ et al, 2001a, b;REICHARDT et al, 2002;SURBT et al, 2006). Außerdem wird die Verbraucherakzeptanz von Rindfleisch durch artgerechte Haltungsverfahren (Mutterkuhhaltung) und den daraus resultierenden Fleischqualitäten beeinflusst (WEIHER und ZUPP, 1997;GOLZE, 2001). Ziel der vorliegenden Untersuchung war die Prüfung des Rasse-bzw.…”
unclassified
See 2 more Smart Citations
“…In this study, rather than review previous experimental results, the results of incorporating estimated growth curves parameters for body weight and dry matter intake were evaluated to present input (feed) and output (body weight gain) relationships. A number of recent reviews have generally concluded that a change in mature body weight has a little effect on the biological efficiency of a meat producing enterprise, because of the associated changes in other feeding and growth parameters (THOMPSON and BARLOW, 1986;ARTHUR et al, 1998;GOLZE, 2001). Consequently, the purposes of the present study were to estimate the growth curve parameters for body weight and dry matter intake of F, LixF and PixF males which individually reared under intensive feeding system and to compare growth rates of these genotypes using body weight and dry matter intake measurements.…”
Section: Introductionmentioning
confidence: 99%